UPAYA MENEMUKAN KONSEP IDEAL TENTANG FUNGSI MAHKAMAH KONSTITUSI - Syahrin, M. Alpi; zulfan, Jufri hardianto; Kastulani, Mhd. (EKSEKUSI, 2019)
AbstrackThe constitutional court in Indonesia was formed to strengthen the guard against democratic development which is expected to transition smoothly and achieve a new democratic national life and relizes the rule of law, because historically the idea of establishing a Constitutional Court by PAH 1 BP MPR  was to go through a transition from an authoritatian regime to an era of democracy. The Constitutional Court is actually not an institution that “menoton” as the guardian of the constitution but must also be able to provide decisions which are certainly the result of the interpretation of the Constitution Court judges who not only issue decisions based on the text alone but the Constitution Court must look at the context that occurs in the mindst of society, so with that the Constitutional Court’s decision was not only oriented to the principle of legal certainty but more than that, namely the principke of legal usefulness. Because the use of the law in the results of decisions of the constitutional institution will be more expected by the public by remembering that the court is a judicial institution whose decisions are binding and final. AbstrakMahkamah Konstitusi di Indonesia dibentuk untuk memperkuat pengawalan terhadap perkembangan demokrasi sehingga diharapkan masa transisi dapat dilalui dengan lancar dan tercapai kehidupan nasional baru yang demokratis dan terwujudnya supremasi hukum, karena sejarahnya gagasan pembentukan Mahkamah Konstitusi oleh PAH I BP MPR untuk melalui masa transisi dari rezim otoriter menuju era demokrasi. Mahkamah Konstitusi sebenarnya bukan lembaga negara yang hanya “menoton” sebagai pengawal konstitusi (the guardian of the constitution) tetapi juga harus mampu memberikan putusan-putusan yang tentunya merupakan hasil dari penafsiran hakim MK yang bukan hanya mengeluarkan keputusan berdasarkan kondisi yang terdapat didalam teks saja melainkan MK harus melihat konteks yang terjadi di tengah-tengah masyarakat, sehingga dengan hal tersebut putusan yang dibuat oleh Mahkamah Konstitusi bukan hanya berorientasi asas kepastian hukum tetapi lebih dari itu yaitu asas kemamfaatan hukum. karena kemamfaatan hukum dalam hal hasil keputusan dari lembaga Mahkamah Konstitusi akan lebih diharapkan oleh masyarakat dengan mengingat bahwa Mahkamah Konstitusi merupakan lembaga peradilan yang keputusanya bersifat mengikat dan final.